Evaluation of Total Phenol, Flavonoid and in vitro Antioxidant Activity of Methanolic Extract of Leaves of Melastoma malabathricum Linn. - Kumar Sharma, Hemanta; Kumar, Atul (Asian Journal of Chemistry, 2010)
Plant containing polyphenols and flavonoids has been reported to possess strong antioxidant properties. Antioxidants are important in protective against various diseases like hypertensive, diabetes, cardiovascular disease and cancer. In present study the antioxidant activity of the methanolic extract of the leaves of Melastoma malabathricum L. was carried out using standard in vitro models. The amount of total phenolic compounds and total flavonoids were also determined by Folin Ciocalteu reagent and aluminium chloride method, respectively. The antioxidant activity was evaluated in vitro by using six different assays viz., reducing power assay, DPPH scavenging activity, hydrogen peroxide scavenging activity, metal chelating assay, nitric oxide scavenging activity and super oxide anion scavenging activity. The result of the study reveals that methanolic extract of the leaves of M. malabathricum possesses antioxidant activity. The activity was found to be concentration dependent. This study will provide ample opportunities for further investigation to verify these activities in vivo.